Short Documentary Film, Urban Art, and Local Memory: Lira Arte Público - Bogas Ríos, María José; Abellán-Hernández, María (Street Art & Urban Creativity, 2024)
This article explores the interplay between public spaces, urban art, identity, and local memory, engaging with new audiovisual formats such as the micro-documentary within the Lira Arte Público audiovisual project. The primary aim of this study is to delve into the themes, spaces, and dialogues that interconnect the city, urban art, and micro-documentaries. Employing a mixed-methods approach that integrates qualitative and quantitative tools, complemented by an analytical-synthetic framework and a narratological perspective, the research analyses the documentary series ‘Muros con Historia-Edición Barrio Arte’. This series consists of six short documentaries, each ranging from four to five minutes in length. The findings elucidate the dual functionality of the series: firstly, as a documentary record enhancing the visibility of the artistic process; and secondly, as a platform for the testimony and affirmation of the identities of the collectives inhabiting the spaces transformed by the mural projects. The study conclusively identifies and discusses how audiovisual language, through both content and form, constructs and conveys the characteristics of the city, mural art, and the Latin American identity of the involved artists.